Preliminary design of an automated rapid maxillary expander for dento-facial application - Sharizli, A.A.; Zabir, F.A.; Abu Osman, Noor Azuan; Radzi, Z.; Shaifizul, A.A. (2007)
The objective of maxillary expansion is to correct maxillo mandibular transverse discrepancies by skeletal (orthopedic) expansion of the maxilla while avoiding any dental side effects. [1]. For a rapid maxillary expansion (RME) device, the expansion of maxilla is accomplished through heavy forces that are capable of separating the midpalatal suture at the rate of 0.2 to 0.5mm per day[1]. This procedure can be done rapidly or slowly depending upon the patient’s age and treatment plan [2]. In this technique, the orthodontist will custom fit an appliance on the upper molars of a patient (Figure 1). Either the patient or the parent will turn the appliance every day throughout a prescribed period. The current expanders are turned by first placing a pin in a tiny hole (capstan). The inserted pin will then push the hole to the rear of the expander. Naturally, the patient is asked to turn the active part of the screw to a certain counts.